Skin fold thickness and its association with milk production performance in Sahiwal cows - BANJARE, SWETA; SANTRA, AJIT KUMAR; PARVEEN, KAISER; MISHRA, SHARAD; SINGH, NISHIMA (The Indian Journal of Animal Sciences, 2025)
The present experiment was conducted at Bull Mother Experimental Farm (BMEF), College of Veterinary Science and Animal Husbandry, Anjora to study the relationship between skin thickness and milk yield of Sahiwal cows. The overall mean skin thickness of neck, dewlap, chest, abdomen, flank, hind quarter, udder and rump was 3.44±0.06, 3.49±0.06, 3.53±0.06, 4.53±0.08, 5.62±0.12, 4.07±0.07, 2.45±0.04 and 6.63±0.17 mm respectively. Analysis of variance showed that that the effect of skin thickness was statistically significant (P<0.01) on total milk yield and daily milk yield. The findings of milk yield in relation to different categories of skin thickness, it was observed that cows total milk yield per lactation was highest for cows with low skin thickness of dewlap (1673.41±95.67 litre) and abdomen (1680.57±99.94 litre). The correlation coefficient between skin thickness of all the sites with daily milk yield was negatively correlated except for abdomen and udder region. Regression coefficient indicated that a decrease in skin thickness by 1 mm would cause an increase in average daily milk yield by 3 to 28 kg.